COT-12 Clinical feature of end-stage glioblastomas. (6th December 2021) - Saito, Norihiko; Hirai, Nozomi; Kushida, Naoki; Sato, Sho; Hiramoto, Yu; Fujita, Satoshi; Nakayama, Haruo; Hayashi, Morito; Ito, Keisuke; Iwabuchi, Satoshi
Abstract: Glioblastoma is the most common and most aggressive primary brain tumor. Even with optimal treatment, tumors repeatedly recur and grow, eventually invading the entire brain. Few studies have evaluated the pathogenesis and pathophysiology of terminal glioblastoma. In this study, we describe the pathological characteristics of 26 glioblastoma cases (including 18 autopsy cases) that were analyzed from initial treatment to confirmation of death at our hospital. The mean age of the 26 patients was 60.7 years, and mean overall survival was 16.7 months. The interval of clinical symptoms from coma to death was 36.2 days, and the interval from onset of respiratory depression to death was 12 days. Steroids and antiepileptic drugs were often continued after completion of active treatment. Psychiatric symptoms and central fever were observed in patients with intrathecal dissemination, and disease progression was rapid in these patients. These patients presented with a variety of symptoms, including psychiatric symptoms, headache, neck pain, and central fever. In addition, a case of diffuse infiltration from the brain parenchyma to the periventricular area in a patient treated with bevacizumab suggested a possible change in the form of recurrence. In the terminal stage of glioblastoma, hypoxemia due to disturbance of the respiratory center results in progression from impaired consciousness to death. Because convulsive seizures are rare when patients are close to death, continuation of antiepileptic drugs may not be necessary. Although many patients develop local recurrences, new treatments may change the mode of recurrence or alter tumor cell characteristics. The number of patients receiving home care and end-of-life care has recently been increasing because of medical improvements, such as home care. Further study of the pathophysiology of glioblastoma may yield better end-of-life care.